Answer:
-2
Step-by-step explanation:
Let x be the unknown value
Log₆ ( 1/36) = x
( 1/36) = 36⁻¹ = (6²)⁻¹ = 6⁻²
Log₆ ( 1/36) = Log₆
6⁻² = -2 Log₆
6
Log₆
6 = 1
-2 Log₆
6 = -2(1) = -2
I think the answer is 176
Answer:
It could be any of them.
Step-by-step explanation:
First off, It could be said that (2c-d)(2c-d) doesn't belong because it includes two subtractions signs and none of the others do.
Secondly, It could be said that (2c+d)(2c-d) doesn't belong because it includes one subtraction sign and one addition sign and none of the others do.
Thirdly, It could be said that (2c+d)(2c+d) doesn't belong because it includes two addition signs, and none of the others do.
Finally, it could be said that (c+d)(c+d) doesn't belong because it doesn't have a multiplying factor of 2 within the parentheses.
I hope this helps :)